2022
DOI: 10.3390/biom12091192
|View full text |Cite
|
Sign up to set email alerts
|

Identification Markers of Carotid Vulnerable Plaques: An Update

Abstract: Vulnerable plaques have been a hot topic in the field of stroke and carotid atherosclerosis. Currently, risk stratification and intervention of carotid plaques are guided by the degree of luminal stenosis. Recently, it has been recognized that the vulnerability of plaques may contribute to the risk of stroke. Some classical interventions, such as carotid endarterectomy, significantly reduce the risk of stroke in symptomatic patients with severe carotid stenosis, while for asymptomatic patients, clinically sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 176 publications
(283 reference statements)
0
9
0
Order By: Relevance
“…Although the precise sequence of lesion progression leading to plaque vulnerability is poorly elucidated, the morphological signs of instability as a potential indicator of stroke risk are well known. This hallmark includes a large lipid core, macrophage-mediated inflammatory changes, intraplaque neoangiogenesis/hemorrhage, ulceration, and microcalcification [ 25 ]. In this context, histological identification of these signs in endarterectomy specimens may provide valuable data concerning underlying plaque morphologies and should guide the treatment strategy to prevent further cerebral events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise sequence of lesion progression leading to plaque vulnerability is poorly elucidated, the morphological signs of instability as a potential indicator of stroke risk are well known. This hallmark includes a large lipid core, macrophage-mediated inflammatory changes, intraplaque neoangiogenesis/hemorrhage, ulceration, and microcalcification [ 25 ]. In this context, histological identification of these signs in endarterectomy specimens may provide valuable data concerning underlying plaque morphologies and should guide the treatment strategy to prevent further cerebral events.…”
Section: Discussionmentioning
confidence: 99%
“…Tomas et al, in 159 carotid specimens obtained by endarterectomy, identified an altered metabolomic signature of unstable carotid plaques, comprising increased glycolysis and amino acid utilization along with low fatty-acid oxidation. A series of pro-inflammatory cytokines, like interleukins IL-1b, IL-6, IL-15, IL-17, and IL-18, are abundantly expressed in homogenates of the cluster characterized by the signature mentioned above [ 25 , 30 ]. Chemokines synthesized by MFs, like monocyte chemoattractant protein-1 (MCP-1) and MF inflammatory protein-1b (MIP-1b) were also up-regulated in unstable vs. stable plaques [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a future prospective study should, next to the leukocyte differential count and other inflammatory biomarkers, at least include carotid MRI and ideally one or several forms of imaging parameters that could detect plaque inflammation, in particular positron emission tomography (PET) CT or dynamic contrast enhanced (DCE-)MRI. The need for more research into plaque vulnerability through these new techniques was recently stressed in a review by Wang et al [ 35 ]. For future research into dynamic MRI techniques, the assistance of deep learning methods has been suggested to aid the determination of plaque vulnerability [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, current clinical practice suggests that not all "high-degree" carotid stenosis have the same risk of cerebrovascular events, and this risk particularly is linked to the morphology and to the composition of the carotid plaque, which define the plaque itself as "vulnerable" or "stable" [22]. Since "vulnerable" plaques have been associated with an increased risk of stroke [23], the preoperative identification of vulnerable lesions is crucial for a proper stratification of the operative risk, with a view to providing a stronger justification for the surgical treatment. Currently, the identification of plaque vulnerability features can only be performed with certainty through histological examination after the surgical removal of the plaque [4].…”
Section: Discussionmentioning
confidence: 99%